An SCR Inverter with Good Regulation and Sine-Wave Output - Mapham, Neville (IEEE transactions on industry and general applications, 1967)
SCR inverters of the sine-wave type are well known. Some have the disadvantages of poor regulation, very high component voltages when operating under heavy load, and an inability to operate with no load.